Sekuritisasi Isu Imigran Oleh Partai Sayap Kanan di Eropa Pasca Covid-19 - Al Farauqi, Mohamad Dziqie Aulia; Aliffatharani, Muhammad Rizzami; Paramitha, Devy Indah (Interdependence Journal of International Studies, 2024)
This research focuses on securitization efforts carried out by right-wing parties in European countries over the presence of immigrants and refugees in their countries' territories. European countries have long been a refuge for refugees and immigrants from various countries. This has led to an increase in the number of foreign citizens in various European countries who are seeking security and obtaining citizenship. Furthermore, after the Covid-19 pandemic that occurred in early 2020 and the conflict between Russia and Ukraine resulted in changes in the flow of voting and the views of the people of European countries regarding the presence of right-wing parties in government. This research uses a descriptive method that will explain the factors that encourage several right-wing political figures in Europe to voice issues regarding the existence of refugees and immigrants who could pose a threat in their region. Through political figures, right-wing parties use narratives and campaigns in an effort to attract and take votes from people who are dissatisfied with the direction of current political policies. Then right-wing parties also try to participate in policy making regarding the presence of immigrants and refugees in their region.